Soviet and post-Soviet Russian criminology – an insider’s reflections - Gilinskij, Jakov Ilʹič (International journal of comparative and applied criminal justice, 2017)
This article provides a reflection on various stages in the development of criminology in Soviet and post-Soviet Russia. I begin with an outline of the key phases of the development of the field as a discipline followed by four critical areas of the developmental processes that include research and academia, as well as emerging areas that are critical for further growth of the field. More specifically, I touch upon the important topics that Russian criminologists pursued in empirical research; exposure to international scholarship and networking; and finally, criminology course offerings in Russian law schools.